Short-term energy supplementation before lambing improves maternal behaviour, udder volume, colostrum viscosity and lamb birthweight in ewes under extensive grazing - Villar, Maria Laura; Giraudo, Celso Gabriel; Cueto, Marcela Isabel (Elsevier, 2023)
The aim of the present experiment was to evaluate the effect of short-term energy supplementation before lambing on maternal and lamb behaviour and colostrum production in a large-scale trial in Merino sheep under extensive grazing. It was hypothesized that prepartum supplementation would improve ewe-lamb bonding at birth, increase udder volume and colostrum production while reducing colostrum viscosity. Milk production between weeks 2 and 5 of lactation was measured to test whether this variable was also affected. A complete randomised designed experiment was conducted over three non-consecutive years (Y1 = 2009, Y2 = 2010, Y3 = 2012) with pregnant adult ewes (Y1: n = 87; Y2: n = 65; Y3: n = 71) from a synchronised mating. Ewes remained under extensive grazing on natural grassland from mating until 5 weeks after lambing. On day 123 of gestation, ewes were randomly assigned to one of two dietary treatments: grazing ewes (Control) or grazing ewes daily supplemented with 250 g of maize and 250 g of oat per head (SUPPL) until day 144 of gestation. Behavioural and performance variables were measured in ewes and lambs. Data showed that SUPPL ewes returned to their offspring more quickly once the newborn was ear-tagged and weighted than Control ewes (P < 0.05). In addition, lambs born to SUPPL ewes tended to suck earlier than Control (P < 0.10). Udder volume in SUPPL ewes was 25% greater than in Control ewes (P < 0.05). Colostrum produced by SUPPL ewes was less viscous than in Control ewes (P < 0.05) and colostrum volume tended to be higher in SUPPL ewes (P < 0.10). Overall, birthweight was significantly greater in lambs born to SUPPL ewes compared with Control (P < 0.05). Milk production between weeks 2 and 5 of lactation was not affected by the dietary treatment (P > 0.05). The present experiment also showed a significant interannual variation in some parameters of interest. A beneficial effect of short-term prepartum supplementation on maternal behaviour, udder volume, colostrum viscosity and lamb birthweight was shown in Merino sheep under extensive grazing. This work also highlights that a practical low-cost supplementation strategy for sheep producers in extensive systems may have clear implications in lamb survival, animal welfare and farm productivity.